GREECE AS A NEW HOMELAND: Studying the Greek pupils’ perceptions on refugees from Syria - BRENTAS , FILIPPOS (IJRDO - Journal of Social Science and Humanities Research, 2020)
The present study focuses on the visual practices and the ways in which the concept of homeland is constructed and interpreted by the Greek pupils regarding to refugees children from Syria. The research material is structured by the visual questionnaires differently for each grade. Methodologically we apply a qualitative research method by collecting visual questionnaires from forty (40) pupils. This research explores the image through visual questionnaires and visual literacy (Imago, 2010, Lieber & Schnell, 2008). The research lasted two (2) weeks in classrooms, one (1) week in the preschool group and one (1) week in elementary school. The parents’ suspicion against the thematic of research was a barrier to the process. The vast majority of parents refused to take part in the survey. Thus many primary schools have been searched in order to find the students composition for the sample. Concluding the research and gathering the results through the answers of the students, proposals can be made for the renewal of Greek education in the direction of an anti-racist pedagogy, free of stereotypes and racial prejudices. Discovering the just definitions for Multicultural education and anti-racist education it leads us to the conclusion of the main differences between the two. The approach of multicultural education seems to be more proactive and encouraging of diversity in a learning environment: anti-racist education has the presumption that racism is already present, and aims to change the actions already involved in the classroom rather than prevent them.